Labor scarcity and women's role in agricultural production: evidence from Bangladesh - de Brauw, Alan (International Food Policy Research Institute, 2019)
Presented by Alan de Brauw (International Food Policy Research Institute), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.